Pollination and fruit set of ‘Rocha’ pears tree grown in Vacaria, RS, Brazil - Luz, Alberto Ramos; Meyer, Geraldine de Andrade; Souza, Deivid Silva de; Rufato, Leo; Kretzchmar, Aike Anneliese (Revista de Ciências Agroveterinárias, 2018)
Representing only 10% of consumption, Brazilian pear production has been stagnating for more than 20 years, at around 20 thousand tons per year, the results of the low cultivated area due to low productivity and consequent low profitability. One of the main causes of the low production of pear orchards is a low fruit set, due to problems in the process of pollination and fertilization of flowers. The objective of this work is to evaluate the natural fruiting process of ‘Rocha’ pear, identifying the rate of open pollination, natural parthenocarpic and self-pollination, as well as to evaluate potential techniques to increase the fruit set of ‘Rocha’ pear, under the climatic conditions in Vacaria, RS. ‘Rocha’ pear trees grafted on the ‘BA 29’ quince rootstock with 'Packham's Triumph' pollinator cultivated in whole rows were used in the proportion of one row of pollinator for three of Rocha cultivar. The effect of controlled pollination with ‘Packham’s Triumph’ and Pyrus calleryana pollen, the effect of the GA3, GA4+7 + BA, TDZ, AVG, plant growth regulators on the fruit set, productivity and fruit quality of ‘Rocha’ pears were studied. It was found that the self-pollination and natural parthenocarpy rates of ‘Rocha’ pear tree and the implanted arrangement do not provide commercially profitable production. The climatic conditions during the flowering, although not favorable, allow the fecundation and fruiting of ‘Rocha’ pear tree in the conditions of study. 20 mg L-1 sprays of TDZ increase fruit set and the productivity of ‘Rocha’ pear trees.